Outbreak Investigation of Diarrheal Diseases in Jajarkot - Bhandari, GP; Dixit, SM; Ghimire, U; Maskey, MK (Journal of Nepal Health Research Council, 2010)
Background: Diarrhea is a major public health problem in Nepal. Recently, there was an outbreak of diarrheal diseases in different districts of mid and far western region of Nepal and the most affected district was Jajarkot. The objective of this study was to detect the causative organism and analyze the epidemic outbreak patterns of diarrhea in selected health institutions in Jajarkot district, Midwestern Region of Nepal, in terms of their demographic characteristics and laboratory findings of stool specimens. Methods: A descriptive study was conducted using secondary data from health institutions of two Village Development committees of Jajarkot. Stool samples were collected purposively to identify the agents of diarrheal diseases. Results: Out of the total 13 stool samples tested, 5 were diagnosed as harboring Vibrio cholerae. The Attack Rate and Case Fatality Ratio were calculated to be 8.2% and 1% respectively for the District. Age groups 15-44 were highly affected; male and female were approximately equally affected. Conclusions: Cholera appears to have been the most important cause for mortality in Jajarkot diarrhea outbreak. The diarrhea outbreak in any districts of Nepal should be closely monitored for the possibility of a Cholera epidemic in the future. Key words: cholera; diarrhea; epidemic; outbreak. DOI: 10.3126/jnhrc.v7i2.3008 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 66-68